2016
DOI: 10.3892/mmr.2016.4823
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of thymoquinone improves cardiovascular function, and attenuates oxidative stress, inflammation and apoptosis by mediating the PI3K/Akt pathway in diabetic rats

Abstract: Thymoquinone is the main active monomer extracted from black cumin and has anti‑inflammatory, antioxidant and anti‑apoptotic functions. However, the protective effects of thymoquinone on cardiovascular function in diabetes remain to be fully elucidated. The present study aimed to investigate the molecular mechanisms underling the beneficial effects of thymoquinone on the cardiovascular function in streptozotocin‑induced diabetes mellitus (DM) rats. Supplement thymoquinone may recover the insulin levels and bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…The phosphatidylinositol-4,5-bisphosphate 3-kinase/protein kinase B (PI3K/Akt) signaling pathway was suppressed in diabetes[53, 54]. Our results showed that TLR4 interfering suppressed the PI3K/Akt pathway, mitigating the abnormal mesangial cell proliferation.…”
Section: Discussionmentioning
confidence: 64%
“…The phosphatidylinositol-4,5-bisphosphate 3-kinase/protein kinase B (PI3K/Akt) signaling pathway was suppressed in diabetes[53, 54]. Our results showed that TLR4 interfering suppressed the PI3K/Akt pathway, mitigating the abnormal mesangial cell proliferation.…”
Section: Discussionmentioning
confidence: 64%
“…The results of the current study demonstrate that thymoquinone treatment contributes to activating PPAR-γ and PI3K/Akt protein expression in SCI rats. Liu et al (39) suggested that thymoquinone improves cardiovascular function, and inhibits inflammation, oxidative stress and apoptosis via the PI3K/Akt pathway in diabetic rats. These results suggest that thymoquinone induces activation of the PI3K/Akt signaling pathway, which may be associated with its protective effect against SCI.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the PI3K/Akt pathway plays a crucial role in the prevention of apoptosis [33]. To investigate the underlying mechanisms of the antiapoptotic effects of the KD, we measured the contents of PI3K, p-Akt and Akt in myocardium samples.…”
Section: Bhb Attenuated High-glucose-induced Apoptosis In Cardiomyocymentioning
confidence: 99%